2016
DOI: 10.3168/jds.2016-10953
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Mid-infrared spectroscopy prediction of fine milk composition and technological properties in Italian Simmental

Abstract: The objective of this study was to evaluate the ability of mid-infrared predictions of fine milk composition and technological traits to serve as a tool for large-scale phenotyping of the Italian Simmental population. Calibration equations accurately predicted the fatty acid profile of the milk, but we obtained moderate or poor accuracy for detailed protein composition, coagulation properties, curd yield and composition, lactoferrin, and concentration of major minerals. To evaluate the role of infrared predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 21 publications
5
40
3
Order By: Relevance
“…Values of RMSEP and R 2 in cross-validation calculated for SFA, SCFA, and C18:0 calibration models are reported in Table 2, and are in agreement with those obtained in previous studies (Soyeurt et al, 2006;Bonfatti et al, 2016).…”
Section: Validation Of the Standardization Proceduressupporting
confidence: 89%
“…Values of RMSEP and R 2 in cross-validation calculated for SFA, SCFA, and C18:0 calibration models are reported in Table 2, and are in agreement with those obtained in previous studies (Soyeurt et al, 2006;Bonfatti et al, 2016).…”
Section: Validation Of the Standardization Proceduressupporting
confidence: 89%
“…The DP method has some benefits over the IP method: there is no need to predict phenotypes from the spectra to estimate the EBV for the traits, and EBV are predicted once (only for the spectra) and then used to derive the EBV of traits. This is particularly relevant when considering the high number of traits for which FTIR calibration equation are being developed (Bonfatti et al, 2016;Gengler et al, 2016). In addition, direct analysis of the spectral variables may increase the precision of the estimated genetic parameters and the accuracy of EBV predictions and genetic gains, particularly for low-heritability traits, as a consequence of exploiting the genetic relationships among many spectral variables (Dagnachew et al, 2013b).…”
Section: Comparison Between Direct and Indirect Methods For Exploitingmentioning
confidence: 99%
“…Calibration equations used in this study were the outcome of a research project (MilCo project, CPDA122982; University of Padova, Padova, Italy), which started in 2013 with the aim of developing proce-dures to estimate EBV for the Italian Simmental cattle population for FTIR predictions of detailed protein and FA composition, minerals, lactoferrin, coagulation properties, cheese yield, and curd composition. Reference data for the development of calibration equations were obtained for milk protein composition by reversed phase HPLC (Bonfatti et al, 2008), for FA composition by accelerated extraction (Dionex application note 345; Thermo Scientific Dionex, 2016) followed by 2-dimensional gas chromatography separation (Pellattiero et al, 2015), for minerals by inductively coupled plasma atomic emission spectroscopy (Soyeurt et al, 2009), for lactoferrin by ELISA (Soyeurt et al, 2007), for milk coagulation properties by lactodynamography (Bonfatti et al, 2016), and for cheese yield and curd composition by micro-cheese making (Bonfatti et al, 2016). In total, 92 traits were measured and calibration equations were developed using more than 1,000 samples for each of the investigated traits, with the exception of minerals (n = 689) and lactoferrin (n = 558).…”
Section: Ftir Spectra and Calibration Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleic acid (18:1n-9, 35.70%) which belongs to VLCFAs is the most abundant fatty acid in beef, followed by palmitic acid (16:0, 31.07%) [4]. With the help of mid-infrared predictions tools, milk was detected to possess more palmitic acid (33.44%) than oleic acid (17.31%) [5]. Lately researches showed that diets high in oleic acid improved the health condition for individuals through the effect on reducing central obesity and cardiovascular disease risk [6, 7].…”
Section: Introductionmentioning
confidence: 99%